Two serious ladies - Bowles, Jane (Dutton, 1984)
Two serious ladies who want to live outside of themselves, Christina Goering and Frieda Copperfield embark on separate quests of salvation. Mrs. Copperfield visits Panama with her husband, where she finds solace among the women who live and work in its brothels. Miss Goering becomes involved with various men. At the end the two women meet again, each transformed by her experience.
Keywords: amériques; approches et analyses; hétérosexisme; panama; personnes lesbiennes; régions géographiques; sexualité; systèmes d'oppressions; thématiques; états-unis